The Evolution of Labour Protection Legislation Following the Enactment of the Labour Creation Act - Arya Bagiastra; Zulkarnain Sitompul; Dedy Ardian Prasetyo (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
This paper examines the development of labour protection laws in Indonesia following the implementation of the Labour Creation Act No. 11 Year 2020. This research is motivated by the controversy and dispute that emerged due to the changes in employment regulation introduced by the law. The new provisions in this law are believed to have negative effects on workers in terms of their pay, working hours, and termination conditions, as compared to the level of protection offered by the Employment Act No. 13 of 2003. This study aims to explore how the legal protection for workers can be maximized following the implementation of the Labour Creation Act. Additionally, it seeks to determine whether joint employment agreements can effectively remedy any deficiencies in the existing legislation. This study employs normative legal research methods, including approaches such as the analysis of legislative regulations, literature review, and case studies. Data is gathered by examining documents and then examined using qualitative methods to determine the effects of regulatory changes on labour protection. Additionally, potential solutions are identified through the use of joint employment agreements. The research findings indicate that the Labour Creation Act generates controversy and conflict between workers and entrepreneurs, particularly on the curtailment of workers' rights. The primary finding of this study is that a collabourative agreement, established in accordance with Article 1338 of the Convention along with Article 1320 of this Convention, can serve as a potent mechanism to rectify the deficiencies in the Creation of Works Act. Nevertheless, a robust and proactive labour union is necessary to guarantee that the agreement offers sufficient safeguards for workers. Hence, enhancing the influence of labour unions and promoting equitable bargaining processes are crucial in attaining a harmonious equilibrium between employers' interests and the safeguarding of workers' rights.